2019
DOI: 10.1029/2019gl082488
|View full text |Cite
|
Sign up to set email alerts
|

Initial Breakdown Pulses Accompanied by VHF Pulses During Negative Cloud‐to‐Ground Lightning Flashes

Abstract: This study compares waveforms recorded by “broadband” very low frequency/low‐frequency/medium‐frequency (VLF/LF/MF) electric field change sensors (bandwidth ~0–2.5 MHz) and very high frequency (VHF) sensors (bandwidth 186–192 MHz) during the initiation of 20 negative cloud‐to‐ground lightning flashes. In the first 2 ms of each flash, initial breakdown (IB) pulses are detected with the VLF/LF/MF sensors. Comparison shows that all classical IB pulses are accompanied by VHF pulses, where classical IB pulses are d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 24 publications
4
15
0
Order By: Relevance
“…We observe a strong correlation between the signal of the broadband antenna and the emitted VHF power, as was already suggested in (Kolmašová et al, 2018(Kolmašová et al, , 2019. The relation between emitted VHF power, the signal of a broadband antenna and interferometry images for the initial leader has been investigated in (Krehbiel, 2017) for New Mexico lightning flashes.…”
Section: Discussionsupporting
confidence: 81%
“…We observe a strong correlation between the signal of the broadband antenna and the emitted VHF power, as was already suggested in (Kolmašová et al, 2018(Kolmašová et al, , 2019. The relation between emitted VHF power, the signal of a broadband antenna and interferometry images for the initial leader has been investigated in (Krehbiel, 2017) for New Mexico lightning flashes.…”
Section: Discussionsupporting
confidence: 81%
“…A study on initial breakdown processes found that 47% of broadband initial breakdown pulses are accompanied by VHF pulses and many VHF pulses have no associated broadband initial breakdown pulses. These observations indicate that the initial lightning leader extends very fast at multiple time scales ranging from submicrosecond to several tens of microseconds (Kolmasova et al, 2019). It was speculated that the VHF radiation is produced by small‐scale positive corona streamers that give rise to the negative breakdowns at a larger scale that are manifested by initial breakdown pulses (Marshall et al, 2019).…”
Section: Comparison Of Camma With Lmamentioning
confidence: 99%
“…It was speculated that the VHF radiation is produced by small‐scale positive corona streamers that give rise to the negative breakdowns at a larger scale that are manifested by initial breakdown pulses (Marshall et al, 2019). While the study of Kolmasova et al (2019) focused on comparisons of LF/VHF radiation produced by lightning during the initial breakdown process, our flash‐to‐flash comparison was looking at LF/VHF radiation sources produced by propagating leaders from initiation to termination. If the simultaneous VHF/LF observations by Kolmasova et al (2019) do suggest the initial leader extends at multiple time and spatial scales, then this study shows this happens throughout the leader processes of the flash, not just during the initial stage of leaders.…”
Section: Comparison Of Camma With Lmamentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, IC occupies approximately three quarters of the total lightning discharges (Rakov & Uman, ), and moreover, IC is considered to be an important predictor in thunderstorm warning, as it usually occurs in the initial phase of thunderstorms before the first cloud‐to‐ground lightning (CG; IEC62793, ). Recent 3‐D lightning observations indicate that many intensive IC processes, such as narrow bipolar event and IBP, and leader in CG follow the approximately vertical channel (Kolmasova et al, ; Kotovsky et al, ; Ushio et al, ). Therefore, it is possible to orientate these discharges by the MDF technique.…”
Section: Introductionmentioning
confidence: 99%